Improvement of the thermo Oxidation properties for low-density polyethylene using curcumin analogues - Ali M. Al-Asadi / Salah Sh. AL-Luaibi*/Basil A. Saleh** ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
In this study, three analogs of curcumin were prepared and used as antioxidant for LDPE. The thermal oxidation inhibition was investigated using carbonyl index, TGA, and DSC as well as the antioxidant inhibition was evaluated using DPPH. The results showed that the curcumin analogs derived from 4-hydroxyl benzaldehyde, compound had high antioxidant efficiency for LDPE. DOI /10.54633/2333-021-042-037